Within-tree variability in the drying properties for blackbutt timber in new south wales - Cabardo, S. J.; Langrish, T. A. G. (Maderas. Ciencia y Tecnología, 2025)
The within-tree variability of drying properties, including the green and final moisture contents, the basic density, and the diffusion coefficient, has been investigated for regrowth blackbutt timber (Eucalyptus pilularis Sm).Timber boards from two regrowth trees were taken from Northern New South Wales in Australia, and dried in a lab scale kiln. The pattern of variation within the two trees was similar, such that the diffusion coefficient was strongly correlated with the initial moisture content and basic density. Principal components analysis suggested that the timber boards with low basic densities and high initial moisture contents had higher diffusion coefficients. A potential reason is that if there is less wood material per unit volume, then this leaves more space for water to occupy, and there is also less resistance for the diffusive transport of moisture. In addition, this suggested correlation was also evident in the analysis of variance (ANOVA). A simulation study, using the timber data measured from the experiments in this paper, was also conducted to estimate how different hardwood drying schedules are likely to affect the distribution of the final moisture contents, and the time taken to reach an average stack moisture content of 0.15 kg/kg. A revised version of the drying schedule used for the experiments in this paper, i.e. adding 5ºC to the dry and wet-bulb temperatures, has been predicted to be a better drying schedule out of the four drying schedules studied, due to it drying the timber quicker as well as having a small dispersion of final moisture contents.